Socio-psychological (characteristic) features of economic socialization and economic culture of the individual - V. Moskalenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article discusses the problem of economic culture as a result of economic socialization. The main focus is on some theoretical concepts, which are the methodological principles of research. In particular, emphasis is placed on the importance of verifying categorical apparatus of the study (discussed relations between the concepts of "culture", "economic culture", and “economic culture of personality"). It is proved that a sign of the "cultural" is "morality”. The meaning of the concept of "efficiency" is defined. "Rationality" as a model of economic behavior and as a sign of "efficiency" in the economic culture is allocated and analyzed. Economic culture of the person is analyzed as gradual inclusion of the individuals in various spheres of economic activities in accordance with their age characteristics. It is shown that the level of economic culture of the person revealed in the fullness of the content of its structural components. A content of cognitive, affective and connotative components of the economic culture of the individual are analyzed. It is shown that the configuration of these components determines the structural features of the economo- psychological characteristics of the individual, which are formed in the process of economic socialization.